Microwave Assisted Alkali Pretreatment of Elephant Grass Using Sodium Hydroxide and Potassium Hydroxide - Syaidatul Akma Mohd Zuki; Norazah Abd Rahman; Nur Aliah Abd Latiff; Noor Fitrah Abu Bakar (International Journal of Integrated Engineering, 2024)
Microwave-assisted alkali pretreatment of Pennisetum purpureum, elephant grass (EG) prior to the hydrolysis process was conducted using sodium hydroxide (NaOH) and potassium hydroxide (KOH) to investigate the effect on lignin content and crystallinity index of cellulose. Microwave-assisted alkali pretreatment of EG was performed using NaOH and KOH at the same concentration of 2.5 M at various residence times of 10, 20, 30, 40 and 60 minutes with a microwave power of 180 W. Lignin content was significantly reduced, measuring 46.08% and 48.9% as the pretreatment time increased at 60 minutes for NaOH and KOH solution, respectively. The optimal condition for the pretreatment was found to be 20 minutes of irradiation, as it resulted in the highest crystallinity index of cellulose at 64.64% and 63.43% for NaOH and KOH pretreatment, respectively.